ABOUT ECOLOGY - Sharopova Muazzam Sobirjonovna (Journal of new century innovations, 2022)
Abstract. It is known that the word "Ecology" has become very popular in recent years. This word is often mentioned when talking about the unfavorable state of the environment. Sometimes this term is used together with words like "Society", "Family", "Human", "Health". Ecology belongs to the group of biological sciences and is currently being formed as a separate science. Also, today the science of ecology is developing in close connection with social life. His field of social ecology was born.